Cobalt Oxide-Modified Titanium Dioxide Nanoparticle Photocatalyst for Degradation of 2,4-Dichlorophenoxyacetic Acid - Leny Yuliati; Nur Azmina Roslan; Wai Ruu Siah; Hendrik Oktendy Lintang (Universitas Gadjah Mada, 2017)
2,4-dichlorophenoxyacetic acid (2,4-D) has been recognized as a possibly carcinogenic compound to human, therefore, 2,4-D should be treated before it is discharged to the environment. Photocatalytic degradation of 2,4-D has been proposed as one of the best methods that offer environmentally safe process. In the present research, titanium dioxide (TiO2) was modified with cobalt oxide (CoO) and tested for photocatalytic degradation of 2,4-D under UV light irradiation. Different amounts of CoO (0.1, 0.5, 1 and 5 mol%) were added onto TiO2 by an impregnation method. The photocatalytic reaction was monitored and analyzed by measurement of 2,4-D absorbance using UV spectrophotometer. After 1 h photocatalytic reaction, it was confirmed that the sample with low loading of 0.1 mol% gave the highest photocatalytic activity among the bare and modified TiO2 photocatalysts. The photocatalytic activity was decreased with the increase of CoO loading, suggesting that the optimum amount of CoO was an important factor to improve the performance of TiO2. Based on fluorescence spectroscopy, such addition of CoO resulted in the reduced emission intensity, which showed the successful decrease in the electron-hole recombination.